Preparation of carbon nanotubes/polyethersulfone antistatic composite materials by a mixing process. Issue 2 (3rd October 2019) - Tian, Yuhan; Zhong, Jiachun; Hu, Linqing; Zheng, Xiaoyi; Cheng, Jie; Pu, Zejun
Abstract: In this work, a facilitated physical dispersion technology was employed to prepare polymer‐based antistatic composites using polyethersulfone (PES) as matrix and the acidulated multiwalled carbon nanotube (MWCNT) as nanofillers, scattering the PES resin in the deionized water contained MWCNT by the colloid mill to obtain MWCNT/PES emulsion and the MWCNT/PES composites were prepared by melt processing. The influence of dispersion technology about the MWCNT/PES composites on the mechanical, thermal, and electrical properties was investigated in detail. The morphology of the MWCNT/PES emulsion was investigated by transmission electron microscopy and scanning electron microscope, respectively. The results showed that the MWCNT nanoparticles were encapsulated in the PES microspheres homogeneously. In addition, the obtained MWCNT/PES composites showed higher glass transition temperature ( T g ) and initial thermal decomposition temperature ( T 5% ). More importantly, the tensile strength and surface resistance of 3 wt% MWCNT/PES composites were up to 112 MPa and 10 6  Ω/m, respectively. Therefore, these high‐performance polymer‐based antistatic composites will have potential application in electronic devices applied with high temperature conditions.